THE IMPACT OF JOB BURNOUT ON EMPLOYEES’ PERFORMANCE - Nicoleta ISAC; Areej Majdi Ahmad HAJ SALEH (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This study is proposed to examine the effects of job burnout on employees’ performance, job satisfaction, turnover intention, and employee engagement in the commercial industry in Istanbul/Turkey. Due to the consequences of job burnout, organizations need to observe factors that lead to burnout to avoid the impact of the job burnout on the performance of employees. Exploring the impact of job burnout phenomenon on employees’ performance was essential in organizations. The primary data was collected via Online Google forms which included 177 participants residing in Istanbul city. Data was collected based on virtual snowball sampling. Spearman correlation analysis was applied to primary data to investigate the job burnout’s impact on the previously mentioned variables. The results find that job burnout had a statistical influence on employee performance, job satisfaction, turnover intention, and employee engagement. According to our results and findings, a negative relationship was found between job burnout and the performance of employee, it was also found a negative relationship between job burnout and job satisfaction, a positive relationship between job burnout and turnover intention, and a negative relationship between job burnout and employee engagement. The conclusion of the research will assist organizations in understanding the causes of job burnout and considering any possible impact burnout may have on employee performance, job satisfaction, turnover intention, and employee engagement.